Application of MCMC-Based Bayesian Modeling for Genetic Evolutionary and Dynamic Change Analysis of Zika Virus - Shao, Tong; Pan, Jiahui; Zhang, Shiwei; Xin, Zhuoyuan; Wang, Guoqing (Frontiers in Genetics, 2020)
Since the zika virus (ZIKV) was first discovered in 1947, it did not produce a large-scale outbreak. However, in the recent years, especially, in 2007 and 2016 there were two episodes of ZIKV outbreaks which have produced serious public health problems. By analyzing the evolution of the viral genome, we can understand the potential for its outbreak. In this study, we constructed a maximum clade credibility (MCC) tree for ZIKV non-structural protein 5 (NS5) gene using Bayesian method. A total of 108 whole-NS5 sequences were retrieved from the GeneBank. Analysis of potential glycosylation, phosphorylation sites of ZIKV virus NS5 gene, and dynamic analysis of gene evolutionary characteristics. Phylogenetic analysis revealed the presence of two sequence lineages: African and Asian. The sequence of strains obtained on Genbank has a high homology, which is 85% to 100%. There are 35 potential phosphorylation sites and glycosylation sites in ZIKV-NS5 sequences. The highest level of genetic diversity for the ZIKV NS5 gene occurred around the year 2016.This article analyzes the possible causes of ZIKV virus outbreaks from the perspective of genetic evolution and analyzes the dynamic trends of virus outbreaks. Provide a theoretical basis for predicting the outbreak of the virus.